Definitive hosts of Spirometra mansonoides (Cestoda, Diphyllobothriidae) in Peru - Tantaleán, Manuel (2005)
A parasitology survey was conducted at the Parque de Las Leyendas Zoo in Lima, Peru at 1993. Forty nine stool samples of animals comprehended among five families of carnivores (Canidae, Ursidae, Procyonidae, Mustelidae, and Felidae) were collected and processed using routine methods for helminth ova detection. Three species of Felidae, Puma concolor, (puma andino and puma de la selva), Panthera onca (jaguar) and Leopardus pardalis (ocelot) had been infected with Spirometra mansonoides.